Nasogastric Decompression vs No Decompression After Pancreaticoduodenectomy: The Randomized Clinical IPOD Trial - Bergeat, Damien (JAMA Surg, 2020)
IMPORTANCE: Although standardization of pancreaticoduodenectomy (PD) has improved postoperative outcomes, morbidity remains high. Fast-track surgery programs appear to improve morbidity, and avoiding nasogastric tube decompression (NGTD), already outdated in most major abdominal surgery, is strongly suggested after PD by fast-track surgery programs but lacks high-level evidence, especially regarding safety. OBJECTIVE: To assess in a randomized clinical trial whether the absence of systematic NGTD after PD reduces postoperative complications. DESIGN, SETTING, AND PARTICIPANTS: The IPOD study (Impact of the Absence of Nasogastric Decompression After Pancreaticoduodenectomy) was an open-label, prospective, single-center, randomized clinical trial conducted at a high-volume pancreatic surgery university hospital in France. In total, 155 patients who were 18 to 75 years of age and required PD for benign or malignant disease were screened for study eligibility. Key exclusion criteria were previous gastric or esophageal surgery and severe comorbidities. Patients were randomly assigned (1:1) to systematic NGTD or to no nasogastric decompression and were followed up until 90 days after surgery. INTERVENTIONS: For patients without NGTD, the NGT was removed immediately after surgery, whereas for patients with NGTD, the NGT was removed 3 to 5 days after surgery. MAIN OUTCOMES AND MEASURES: The primary end point was the occurrence of postoperative complications grade II or higher using the Clavien-Dindo classification. The primary end point and safety were evaluated in the intent-to-treat population. RESULTS: From January 2016 to August 2018, 125 screened patients were considered eligible for the study, and 111 were randomized to no NGTD (n = 52) or to NGTD (n = 59). No patient was lost to follow-up. The 2 groups had similar patient demographic and clinical characteristics at baseline. The median (interquartile range) age was 63.0 (57.0-66.5) years in the group with NGTD (38 [64.4%] were males) and 64.0 (58.0-68.0) years in the group without NGTD (31 [59.6%] were males). The postoperative complication rates grade II or higher were similar between the 2 groups (risk ratio, 0.99; 95% CI, 0.66-1.47; P > .99). Pulmonary complication rates (risk ratio, 0.59; 95% CI, 0.18-1.95; P = .44) and delayed gastric emptying rates (risk ratio, 1.07; 95% CI, 0.52-2.21; P > .99) were not significantly different between the groups. Median (interquartile) length of hospital stay for patients without NGTD was not significantly different compared with those with NGTD (10.0 [9.0-16.3] vs 12.0 [10.0-16.0] days; P = .14). CONCLUSIONS AND RELEVANCE: The present study found no significant difference in postoperative complication occurrence of Clavien-Dindo classification grade II or higher between systematic NGTD and no NGTD after PD, suggesting that avoiding systematic nasogastric decompression is safe for this indication. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02594956